Chemical speciation and bioavailability of potentially toxic elements in surface sediment from the Huaihe River, Anhui Province, China. (March 2023) - You, Mu; Hu, Yunhu; Meng, Ying
Abstract: In order to understand the characteristics of speciation and ecological risk of potentially toxic element (PTE) pollution in the surface sediment of huaihe river (Anhui province), 23 surface sediment samples were collected. The occurrence characteristics of PTEs (As, Cr, Zn, Cu, Cd, Pb, Mn) were analyzed by modified continuous extraction method (BCR), and the pollution status and potential ecological risk of PTEs were comprehensively evaluated by Pollution Load Index (PLI), Geoaccumulation Index ( Igeo ), Enrichment Factor (EF) and the risk assessment code (RAC). Results showed that the total concentrations of As, Mn, Cd, Cr, Cu, Pb, and Zn in sediment were 14.98 ± 2.32, 936.02 ± 144.48, 0.32 ± 0.08, 161.73 ± 124.83, 40.44 ± 9.67, 15.46 ± 6.67, and 74.85 ± 26.43 mg/kg, respectively. The mean concentrations of PTEs with the increasing order of Zn < Mn < Cr < Pb < Cu < As < Cd. Most PTEs appeared to mainly associate with a dominant proportion of residual fraction suggesting lower mobility whereas Cd and Mn presented a relative higher exchangeable fraction indicating a great degree of bioavailability and easily ingested by aquatic organism. Results of pollution degree showed that 3 sampling sites belong to the pollution degree of strong pollution, and the other sampling sites belonged to the medium pollution level. The indexes EF revealed moderately enrichment of Cr, minor enrichment of Cd, Mn and As, no enrichment of Cu, Zn and Pb. The values of the Igeo and RAC demonstrated that Cd and Mn pose a high ecological risk, which deserves further attention. Highlights: Potentially toxic elements (PTEs) in the sediment exceed the background value, except Pb and Zn. The distribution characteristics of PTEs are related to the distribution of pollution sources, mainly related to mining activities and power plants. The fractions of PTEs varied greatly in the surface sediment. The indexes of EF, Igeo and RAC confirmed that PTEs with high values and large labile states with more ecological risk and mobile to aquatic organisms.